Emerging applications of metal–organic frameworks. Issue 35 (6th July 2016) - Ricco, Raffaele; Pfeiffer, Constance; Sumida, Kenji; Sumby, Christopher J.; Falcaro, Paolo; Furukawa, Shuhei; Champness, Neil R.; Doonan, Christian J.
Abstract : Metal–organic frameworks are highly crystalline porous materials which present emerging opportunities in biotechnology, catalysis, microelectronics and photonics. Abstract : Metal–organic frameworks are a unique class of materials well known for their crystallinity and ultra-high porosity. Since their first report over fifteen years ago, research in this area has sought to actively exploit these properties, especially in gas adsorption. In this article we canvass some emerging topics in the field of MOF research that show promise for new applications in areas such as biotechnology, catalysis, and microelectronics.